Expansion of Murine Periosteal Progenitor Cells with Fibroblast Growth Factor 2 Reveals an Intrinsic Endochondral Ossification Program Mediated by Bone Morphogenetic Protein 2. (18th August 2014) - van Gastel, Nick; Stegen, Steve; Stockmans, Ingrid; Moermans, Karen; Schrooten, Jan; Graf, Daniel; Luyten, Frank P.; Carmeliet, Geert
Abstract : The preservation of the bone-forming potential of skeletal progenitor cells during their ex vivo expansion remains one of the major challenges for cell-based bone regeneration strategies. We report that expansion of murine periosteal cells in the presence of FGF2, a signal present during the early stages of fracture healing, is necessary and sufficient to maintain their ability to organize in vivo into a cartilage template which gives rise to mature bone. Implantation of FGF2-primed cells in a large bone defect in mice resulted in complete healing, demonstrating the feasibility of using this approach for bone tissue engineering purposes. Mechanistically, the enhanced endochondral ossification potential of FGF2-expanded periosteal cells is predominantly driven by an increased production of BMP2 and is additionally linked to an improved preservation of skeletal progenitor cells in the cultures. This characteristic is unique for periosteal cells, as FGF2-primed bone marrow stromal cells formed significantly less bone and progressed exclusively through the intramembranous pathway, revealing essential differences between both cell pools. Taken together, our findings provide insight in the molecular regulation of fracture repair by identifying a unique interaction between periosteal cells and FGF2. These insights may promote the development of cell-based therapeutic strategies for bone regeneration which are independent of the in vivo use of growth factors, thus limiting undesired side effects. Stem Cells   2014;32:2407–2418